2019
DOI: 10.1002/chem.201903931
|View full text |Cite
|
Sign up to set email alerts
|

The Role of LiBr and ZnBr2 on the Cross‐Coupling of Aryl Bromides with Bu2Zn or BuZnBr

Abstract: The impact of LiBr and ZnBr2 salts on the Negishi coupling of alkylZnBr and dialkylzinc nucleophiles with both electron‐rich and ‐poor aryl electrophiles has been examined. Focusing only on the more difficult coupling of deactivated (electron‐rich) oxidative addition partners, LiBr promotes coupling with BuZnBr, but does not have such an effect with Bu2Zn. The presence of exogenous ZnBr2 shuts down the coupling of both BuZnBr and Bu2Zn, which has been shown before with alkyl electrophiles. Strikingly, the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…While zinc salts certainly sequester free halides that can at times be crucial for coupling, recent studies have provided insights into some other harmful effects zinc salts have on Negishi coupling. In 2019 Organ published an investigation on an aryl−alkyl coupling that showed no dependence on LiBr [43] . The coupling of 50 a with salt‐free n ‐Bu 2 Zn ( 1 ) was studied as a model reaction for a challenging coupling due to the electron rich electrophile and the Lewis basic amine that can coordinate readily to palladium.…”
Section: Role Of Znx2 Salts In the Negishi Reactionmentioning
confidence: 99%
“…While zinc salts certainly sequester free halides that can at times be crucial for coupling, recent studies have provided insights into some other harmful effects zinc salts have on Negishi coupling. In 2019 Organ published an investigation on an aryl−alkyl coupling that showed no dependence on LiBr [43] . The coupling of 50 a with salt‐free n ‐Bu 2 Zn ( 1 ) was studied as a model reaction for a challenging coupling due to the electron rich electrophile and the Lewis basic amine that can coordinate readily to palladium.…”
Section: Role Of Znx2 Salts In the Negishi Reactionmentioning
confidence: 99%
“…[7,8,9] The coordination of anions to the organozinc species leads to anionic species "zincates", whose exact composition is not always easily established, and whose reactivity differs substantially from neutral organozinc reagents. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Finally, the halogen coordinated to the zinc in haloorganozinc reagents, (whose halogen may proceed from any of the reagents used in its synthesis), also plays a relevant role. A. Lei et al carried out mechanistic studies using in situ IR and X-Ray…”
Section: Introductionmentioning
confidence: 99%
“…The isomerization catalyzed by poor nucleophiles, such as [ZnCl2(solv)2] remains unproven until now, although the role of zinc halides in other steps of the Negishi reaction has been reported. [25] In this work we study the effect of the ligand in solution on the transmetalation between trans-…”
Section: Introductionmentioning
confidence: 99%
“…[8] Initially,i tw as viewed that their presence was not problematic-ironically,t heir presence is essential for any coupling to take place at all. [9] We, [9,10] and others, [6,11] have proposed the interplay between LiBr with the alkylzinc reagent to form zincates that, through heightened nucleophilicity,h elp drive the TM step of the cross-coupling catalytic cycle. We have found that arylzinch a-lides also require LiBr to couple.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have proposed the interplay between LiBr with the alkylzinc reagent to form zincates that, through heightened nucleophilicity, help drive the TM step of the cross‐coupling catalytic cycle. We have found that arylzinc halides also require LiBr to couple .…”
Section: Introductionmentioning
confidence: 99%